Comprehensive Ecological and Geographic Characterization of Eukaryotic and Prokaryotic Microbiomes in African Anopheles - Cuesta, Eugeni Belda; Coulibaly, Boubacar; Bukhari, Tullu; Eiglmeier, Karin; Kone, Raymond; Coulibaly, Mamadou B.; Zongo, Soumanaba; Barry, Mamadou; Gneme, Awa; Guelbeogo, Wamdaogo M.; Beavogui, Abdoul H.; Traore, Sekou F.; et al. (Frontiers in Microbiology, 2021)
Exposure of mosquitoes to numerous eukaryotic and prokaryotic microbes in their associated microbiomes has probably helped drive the evolution of the innate immune system. To our knowledge, a metagenomic catalogue of the eukaryotic microbiome has not been reported from any insect. Here we employ a novel approach to preferentially deplete host 18S ribosomal RNA gene amplicons to reveal the composition of the eukaryotic microbial communities of Anopheles larvae sampled in Kenya, Burkina Faso and Republic of Guinea (Conakry). We identified 453 eukaryotic operational taxonomic units (OTUs) associated with Anopheles larvae in nature, but an average of 45% of the 18S rRNA sequences clustered into OTUs that lacked a taxonomic assignment in the Silva database. Thus, the Anopheles microbiome contains a striking proportion of novel eukaryotic taxa. Using sequence similarity matching and de novo phylogenetic placement, the fraction of unassigned sequences was reduced to an average of 4%, and many unclassified OTUs were assigned as relatives of known taxa. A novel taxon of the genus Ophryocystis in the phylum Apicomplexa (which also includes Plasmodium) is widespread in Anopheles larvae from East and West Africa. Notably, Ophryocystis is present at fluctuating abundance among larval breeding sites, consistent with the expected pattern of an epidemic pathogen. Species richness of the eukaryotic microbiome was not significantly different across sites from East to West Africa, while species richness of the prokaryotic microbiome was significantly lower in West Africa. Laboratory colonies of Anopheles coluzzii harbor 26 eukaryotic OTUs, of which 38% (n=10) are shared with wild populations, while 16 OTUs are unique to the laboratory colonies. Genetically distinct An. coluzzii colonies co-housed in the same facility maintain different prokaryotic microbiome profiles, suggesting a persistent host genetic influence on microbiome composition. These results provide a foundation to understand the role of the Anopheles eukaryotic microbiome in vector immunity and pathogen transmission. We hypothesize that prevalent apicomplexans such as Ophryocystis associated with Anopheles could induce interference or competition against Plasmodium within the vector. This and other members of the eukaryotic microbiome may offer candidates for new vector control tools.